2020
DOI: 10.1111/apt.15890
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the biphasic kinetics of serum HBV RNA in patients with HBeAg‐positive chronic hepatitis B treated with nucleos(t)ide analogues

Abstract: Summary Background Serum hepatitis B virus (HBV) RNA is a novel biomarker for evaluating treatment response. Detailed information regarding serum HBV RNA kinetics during treatment with nucleos(t)ide analogues (NAs) is limited. Aims To ascertain serum HBV RNA kinetics during long‐term NA treatment and identify associated factors. Methods We enrolled 76 HBeAg‐positive chronic hepatitis B patients receiving NA from randomised controlled trials. Laboratory assays were undertaken every 3 months. Factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 37 publications
3
31
1
Order By: Relevance
“…This finding, consistent with the observed measurements in vitro and in transgenic mice, 5 enhances the current knowledge of HBV RNA kinetics under NA therapy. In particular, we show that HBV RNA may transiently increase in the first days of treatment reflecting the accumulation of pgRNA in infected cells before decreasing in the long run as shown by Liu et al 33 Our model also predicted that NA treatment leads to an increase in the ratio of HBV RNA/HBV DNA, from 0.01 at baseline to up to 100 after a couple of weeks (Figure 5). 5,7 Interestingly, we predicted that this increase was also likely to occur during treatment combination of CpAM + NA.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding, consistent with the observed measurements in vitro and in transgenic mice, 5 enhances the current knowledge of HBV RNA kinetics under NA therapy. In particular, we show that HBV RNA may transiently increase in the first days of treatment reflecting the accumulation of pgRNA in infected cells before decreasing in the long run as shown by Liu et al 33 Our model also predicted that NA treatment leads to an increase in the ratio of HBV RNA/HBV DNA, from 0.01 at baseline to up to 100 after a couple of weeks (Figure 5). 5,7 Interestingly, we predicted that this increase was also likely to occur during treatment combination of CpAM + NA.…”
Section: Discussionsupporting
confidence: 80%
“…After this initial decline, both HBV RNA and HBV DNA declined at a slower rate, reflecting the progressive loss of productively infected cells, with a half-life of 5.3 days. 33 Our model also predicted that NA treatment leads to an increase in the ratio of HBV RNA/HBV DNA, from 0.01 at baseline to up to 100 after a couple of weeks ( Figure 5). 5,7 Interestingly, we predicted that this increase was also likely to occur during treatment combination of CpAM + NA.…”
Section: Discussionmentioning
confidence: 54%
“…Different from this study, we have recently quantified serum HBV RNA and DNA in 304 patients with treatment‐naïve chronic hepatitis B using our in‐house assays targeting the S region and calibrated with our in‐house HBV‐DNA standard. ( 4 ) Our results showed that the median level of serum HBV RNA was higher than that of HBV DNA by 0.49 log 10 copies/mL ( P < 0.001), inconsistent with the finding of higher median level of serum HBV DNA than HBV RNA in the study by Mak et al…”
Section: Figcontrasting
confidence: 99%
“…Interestingly, in Liu et al5 some NA-treated patients had sRNA and sDNA declines of a similar magnitude as early as 12 weeks of therapy which cannot be predicted by Goncalves et al model. Larger and more detailed kinetic studies are needed to characterize early sRNA kinetics under NA in humans, which may provide an opportunity to examine the HBV-host dynamics and NA mode of actions proposed by Goncalves and colleagues that drives sRNA dynamics.…”
mentioning
confidence: 83%